Frequency of Scrotal Pathologies on Ultrasound Associated with Benign Prostatic Hyperplasia - Muhammad Usama Bashir, Muhammad Uzair, Syed Muhammad Yousaf Farooq, Mujeeb Ur Rehman, Muhammad Hussain, Hazrat Umar, Hafiz Muhammad Uzair, Tawab Ullah, Tariq Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Men's lower urinary tract symptoms are frequently caused by benign prostatic hyperplasia (BPH), which is the non-cancerous expansion or hyperplasia of prostate tissue. In these patients, a accurate diagnosis of testicular pathologies and the avoidance of testicular infarction are of highest importance. Duration of study: study was conducted from January 2022, till June 2022. Place of study: Department of Radiology, Sheikh Zayed medical college and hospital Lahore, Pakistan Study design: A cross-sectional study. Objective: To find the frequency of scrotal pathologies on ultra sound in benign prostatic hyperplasia patients Methodology: A cross sectional study was conducted at Department of Radiology, Sheikh Zayed medical college and hospital Lahore, Pakistan (SZMC). SPSS version 21.0 was used for data analysis. The inclusion criteria for present study considered the enlargement of prostate gland in men with age which is very common. Uncomfortable urinary symptoms, such as a bladder blockage, might be brought on by an enlarged prostate gland. It may also result in issues with the kidney, urinary system and bladder. The exclusion criteria were patients who had any history of previous testicular pathology and men who were uncooperative. Frequency of scrotal pathologies in patients with benign prostatic hyperplasia were calculated by using ultrasound machine Mindray Z5 and Toshiba Xario 100 with linear probe of 7.5-11MHz were used. Results: In current study 159 men with benign prostatic hyperplasia visiting radiology department for ultrasound were included. Out of 159 men with BPH, 37(23.3%) had epididymal cysts, 24(15.1%) had undescended testis, 18(11.3%) had epidydmo-orchitis, 39(24.5%) had epididmytis, 22(13.8%) had microlithiasis, 37(23.3%) had varicocele, 85(53.3%) had hydrocele and 32(20.1%) patients had normal scrotal findings. In patients with no epididymitis mean value of Prevoid was 376 ml and post void were 49 ml and prostate volume was 49 grams. In patients with epididymitis mean value of Prevoid was 377 ml and post void were 48 ml and prostate volume was 46 grams respectively. Practical implication: This research is very informative for men community regarding urological complications especially about enlargement of prostate gland and its complications. Conclusion: Our study concluded that, most patients coming with BPH had scrotal pathologies. Hydrocele was most common pathology in patients with BPH. Keywords: Scrotal Ultrasound, Hydrocele, Varicocele, Ultrasonography, Hyperplasia, Prostate gland, Epididymitis, Microlithiasis